THE EFFECT OF SELF REGULATED LEARNING MODEL TOWARDS THE PHYSICS CONCEPT UNDERSTANDING OF THE 8TH GRADE STUDENTS OF SMP NEGERI 1 UBUD IN THE ACADEMIC YEAR 2013/2014 - ., I Made Adi Wiadnyana; ., Prof. Dr. Ketut Suma, MS; ., Putu Artawan, S.Pd. (Jurnal Pendidikan Fisika Undiksha, 2014)
Penelitian ini bertujuan untuk menganalisis perbedaan pemahaman konsep fisika antara kelompok siswa yang belajar dengan model self regulated learning (MSRL) dan kelompok siswa yang belajar dengan model pembelajaran direct instruction (MPDI). Jenis penelitian ini adalah eksperimental semu dengan desain penelitian nonequivalent pretest-posttest control group design. Variabel bebas pada penelitian ini adalah model self regulated learning dan model direct instruction sedangkan variabel terikatnya adalah pemahaman konsep fisika siswa. Populasi penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 1 Ubud tahun pelajaran 2013/2014 yang terdiri dari 9 kelas dengan jumlah populasi 248 siswa. Sampel kelompok diambil dengan teknik simple random sampling. Jumlah sampel dalam penelitian ini adalah 108 siswa, di mana 55 siswa pada kelompok MSRL (VIIID dan VIIIE) dan 53 siswa pada kelompok MPDI (VIIIF dan VIIIG). Teknik pengumpulan data dilakukan dengan pretest dan posttest. Data pemahaman konsep fisika siswa dianalisis secara deskriptif dan analisis varians satu jalur, dengan pengujian taraf signifikansi 0,05. Hasil penelitian menunjukkan terdapat perbedaan pemahaman konsep antara kelompok siswa yang belajar menggunakan MSRL dan MPDI (F = 23,196 dan α = 0,001). Pemahaman konsep fisika siswa yang belajar dengan menggunakan MSRL berada pada kualifikasi baik (M = 75,21 dan SD = 8,50) sedangkan pemahaman konsep fisika siswa yang belajar dengan menggunakan MPDI berada pada kualifikasi cukup (M = 59,43 dan SD = 12,00). Hasil ini menunjukkan bahwa pemahaman konsep fisika kelompok siswa yang belajar dengan menggunakan MSRL relatif lebih tinggi dibandingkan kelompok siswa yang belajar dengan menggunakan MPDI. Kata Kunci : model self regulated learning, model pembelajaran direct instruction, pemahaman konsep fisika. This study aimed at analyzing the difference of physics concept understanding between the groups of students who studied with self regulated learning model (SRLM) and the student who studied with direct instruction learning model (DILM). This study was quasy experiment with using non equivalent pretest-posttest control group design. The independent variables on this research were self regulated learning model and direct instruction model, meanwhile the dependent variable was physics concept understanding. The population of this research was the whole students of grade VIII of SMP Negeri 1 Ubud in the academic year 2013/2014 which consisted of 248 students from 9 classes. Group of samples were taken by using simple random sampling technique. The amount of samples in this research were 108 students in which 55 students were from the SRLM group (class VIIID and VIIIE) and 53 students were from DILM group (class VIIIF and VIIIG). The techniques used for collecting data were pretest and posttest. The data of students’ physics concept understanding were analyzed descriptively and using one way variance analysis, with the significant evaluation level was 0.05. The result shows that there is a difference of physics concept understanding between group of SRLM students and group of DILM students (F= 23.196 and α= 0.001). The physics concept understanding on the SRLM students was categorized "good"(M=75.21 and SD=8.50), meanwhile the physics concept understanding on the DILM students was categorized "fair" (M=59.43 and SD=12.00). This result shows that the physics concept understanding of the group of SRLM students is higher than of the group of DILM students. keyword : Self regulated learning model, Direct instruction learning model, Physics concept understanding